The limits of soft-power public diplomacy - Car, Viktorija (Teorija in praksa, 2016)
In international relations the role of public diplomacy, inter alia, is to brand the country and the nation through its culture and art. In Indian foreign policy, as a tool of "soft power" diplomacy, Bollywood has always been one of the most influential tools of promotion of national culture, heritage and tradition. In this paper authors present the results of the survey on consumption and reception of Bollywood movies among students of media and communications studies and of political science of the University of Zagreb. The conclusion is that Croatian students of media, communication and political science "read" Bollywood films through lenses of stereotypes.
Keywords: Bollywood; Consumption; Croatia; Diplomacija; Diplomacy; družba; Film; Hrvaška; India; Indija; indijski film; Potrošnja; society; Students; Študentje